The nature of interpretive phenomenological reflective practice for junior doctors. Issue 5 (3rd September 2019) - Law, Richard Wai Ming; Shafey, Omar
ABSTRACT: The role of reflective practice in clinical professional development has been demonstrated in the extant literature to be relevant and important. As a cognitive strategy, reflection allows clinicians to inform their ability to collect and process complex information; make sound clinical judgements; deliver patient-centred care and learn from medical mistakes. Therefore, learning from reflection is necessary for lifelong and continual professional development. The imperative to derive meaning from clinical practice makes reflection an important aspect of clinical training. Indeed, reflection compels the practitioner to question one's already held professional values and attitudes during the mental capture of clinical experience. Interpretive phenomenology is a useful approach for enhancing the understanding of lived experiences. This paradigm has been much under-utilised in medical education. Understanding reflective practice for clinicians from an interpretive phenomenological perspective serves to create the potential for linking theory and practice within the context of professionalism and clinical responsibility. This article attempts to demonstrate the efficacy of interpretive phenomenological perspective to reflective practice within the context of clinical training, medical education, and on becoming effective reflective practitioners.